Settler colonialism in the twentieth century : projects, practices, legacies - Elkins, Caroline; Pedersen, Susan (Routledge, 2005)
Postcolonial states and metropolitan societies still grapple today with the divisive and difficult legacies unleashed by settler colonialism.Whether they were settled for trade or geopolitical reasons, these settler communities had in common their shaping of landholding, laws, and race relations in colonies throughout the world. By looking at the detail of settlements in the twentieth century--from European colonial projects in Africa and expansionist efforts by the Japanese in Korea and Manchuria, to the Germans in Poland and the historical trajectories of Israel/Palestine and South A
Keywords: Colonization : History : 20th century; Emigration and immigration : History : 20th century; Ethnic relations : History : 20th century